O Teorema de classificação de superfícies fechadas - Souza, Gustavo Luciano de (Universidade Federal de São Carlos, 2022)
In this work we will study some concepts of algebraic topology such as fundamental group and simplicial complexes, then we will present a proof of the closed surface classification theorem.
The classification Theorem of closed surfaces
Keywords: Topologia; Superfície; Complexo simplicial; Grupo fundamental; CIENCIAS EXATAS E DA TERRA::MATEMATICA::GEOMETRIA E TOPOLOGIA::TOPOLOGIA ALGEBRICA